Proton pump inhibitors: the impact on cognitive health in older adults - Ramírez Álvarez, Alexander (2024)
Proton pump inhibitors (PPIs) are the most potent drugs to inhibit gastric acid secretion, being used in the treatment of most inflammatory conditions of the gastric mucosa. They are among the most prescribed and overprescribed medications worldwide; for example, in the United States, according to the National Health and Nutrition Examination Survey, they almost doubled their use in adults aged 40 years and older from 4.9 % to 8.3 % between 1999 and 2012. Although they are generally considered well tolerated, some epidemiological studies extracting information from large databases have reported a number of adverse effects associated with their prolonged use, including cognitive impairment, chronic kidney disease, myocardial infarction, stroke, bone fractures and even death, among others. The objective was to conduct a narrative review of the literature on the effects of chronic use of PPIs on cognitive impairment in older adults. Articles were reviewed based on a search in the PubMed, Scopus and SciELO databases using both English and Spanish keywords and related MeSH/DeCS terms. Neurological side effects induced by chronic PPI use may be indirectly related to secondary systemic disorders (magnesium and vitamin B12 deficiency) or to direct effects on neuronal functioning after passing through the blood-brain barrier. Although several neurobiological mechanisms by which PPIs could favor the development of dementia—which involve Tau protein function, beta-amyloid [βA] accumulation and cobalamin deficiency, among others—have been described, most of the available clinical evidence has not shown a significant association between PPI use and the risk of dementia or cognitive impairment. To establish the adverse clinical effects of chronic PPI use more clearly, especially on brain functioning, well-designed cohort studies with large sample sizes and long follow-up periods, with a reliable method to adjust for standardized confounders, as well as subgroup analyses are needed.